PENGARUH DESAIN PRODUK, CITRA MEREK DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN SEPATU OLAHRAGA MEREK ADIDAS (Studi pada Mahasiswa FEB Universitas Satya Negara Indonesia) - Fahri Rehansyah; Lucy Nancy Simatupang (Jurnal Manajemen, 2023)
This study aims to determine the Influence of Product Design, Brand Image, and Lifestyle on the Purchasing Decision of Adidas brand sports shoes on Students of the Faculty of Economics and Business, Satya Negara University Indonesia. The data used is primary data collected through the distribution of questionnaires to 110 students who use Adidas brand sports shoes. The method used in this study used quantitative methods with causal design and research results based on respondents' answers using the Likert scale. The data analysis methods used in this study are the Multiple Linear Regression Test, F Test, t Test, and Coefficient of Determination.The results of this study show that simultaneously (test F) Product Design, Brand Image, and Lifestyle affect Purchasing Decisions. Partially (test t) Product Design does not affect the Purchase Decision, Brand Image affects the Purchase Decision, and Lifestyle affects the Purchase Decision.